Landslide Susceptibility in Relation to Correlation of Groundwater Development and Ground Condition - S. N. L. Taib; O. S. Selaman; C. L. Chen; R. Lim; D. S. Awang Ismail (Advances in Civil Engineering)
Rainfall is inevitably one of the main factors that trigger landslides. However, not much study has been conducted on the impact of groundwater rise on slope stability. Thus, this study is intended to focus on the rise of the groundwater level from the bottom of the slope which would lead to landslides due to pore pressure development by eliminating other landslide-triggering factors (i.e., infiltration and surface runoff). Saturated sand was used for slope modeling, and sand densities of 1523 kg/m3, 1562 kg/m3, and 1592 kg/m3 were tested with a constant slope angle of 45°. Another set of experiments was also performed on slopes having angles of 25°, 45°, and 60° and with a maintained density of sand at 1562 kg/m3. Through observation, failure was initiated first at the toe of the slope before minor and major slips or total collapse occurs. Dimensions of slip surfaces were measured and included in SLOPE/W for the computation of the safety factor. In conclusion, safety factors are found to be higher in denser soil and in the lowest slope angle. However, faster occurrence of collapse in denser soil was identified and could be contributed by the faster pore water pressure development.